A novel high performance composite anode with in situ growth of Fe-Ni alloy nanoparticles for intermediate solid oxide fuel cells. (1st May 2017) - Li, Jingcheng; Yu, Yan; Yin, Yi-Mei; Zhou, Ning; Ma, Zi-Feng
Graphical abstract: Highlights: A composite anode with endogenous Fe-Ni alloy nanoparticles has been prepared. The redox reversibility of the anode has been confirmed by XRD. The Ea of H2 oxidation at the anode is much smaller than that at Ni-YSZ anode. A ScSZ supported cell achieves MPD of 0.71 Wcm −2 and Rp of 0.16 Ω cm 2 at 800 °C. The single cell shows stable output during 105 h testing at 800 °C 0.7 V in wet H2 . Abstract: A redox reversible composite anode with Fe-Ni alloy nanoparticles in situ growth on SrLaFeO4 -type and LaFeO3 -type oxide substrates has been prepared for intermediate temperature solid oxide fuel cell (IT-SOFC) by reducing perovskite precursor La0.4 Sr0.6 Fe0.75 Ni0.1 Nb0.15 O3-δ (LSFNNb) in wet H2 at 900 °C for 1 h. The anode has shown an excellent electrochemical catalytic activity for oxidation of hydrogen with much smaller Ea (25.1 ∼ 68.9 kJ mol −1 ) than the value (>160 kJ mol −1 ) at Ni-YSZ anode. A scandium stabilized zirconia (ScSZ) electrolyte supported SOFC with the anode achieves maximum power densities of 0.71, 0.52, 0.35, and 0.21 W cm −2 at 800, 750, 700 and 650 °C, respectively in wet H2 (3% H2 O), and the corresponding Rp of 0.16, 0.21, 0.35, and 0.60 Ω cm 2 under OCV. Moreover, the single cell shows stable power output during ∼105 h operation at 800 °C under 0.7 V in wet H2 after a initial degradation, indicating that R-LSFNNb is an excellent candidate as anode of IT-SOFC.